2022
DOI: 10.1097/md.0000000000031633
|View full text |Cite
|
Sign up to set email alerts
|

Influence of handrail height and knee joint support on sit-to-stand movement

Abstract: Handrail height and knee joint support both significantly influence sit-to-stand (STS) movement. However, research on the associations between handrail height, knee joint support, and their cumulative effect on STS kinematics and changes in plantar pressure distribution during STS under different handrail heights and knee joint support is still unclear. The main objective of this study was to examine the influence of handrail height and knee joint support on the kinematics and the distribution of plantar press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[10][11][12] Some studies have shown that the STS motion is easily affected by the initial sitting posture, [13,14] including adjusting the height of the chair, increasing the trunk flexion and changing the initial foot position. [15,16] Shoichi Kawagoe et al [17] studied the influence of foot fore-and-aft positioning on dynamics during STS transfer. In their study, they found that it will directly affect the horizontal displacement of the COG and reduce the stability of the body when the foot is in the front.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Some studies have shown that the STS motion is easily affected by the initial sitting posture, [13,14] including adjusting the height of the chair, increasing the trunk flexion and changing the initial foot position. [15,16] Shoichi Kawagoe et al [17] studied the influence of foot fore-and-aft positioning on dynamics during STS transfer. In their study, they found that it will directly affect the horizontal displacement of the COG and reduce the stability of the body when the foot is in the front.…”
Section: Introductionmentioning
confidence: 99%